Generation and Characterization of UL21-Null Herpes Simplex Virus Type 1 - Muto, Yoshifumi; Goshima, Fumi; Ushijima, Yoko; Kimura, Hiroshi; Nishiyama, Yukihiro (Frontiers in Microbiology, 2012)
UL21 of herpes simplex virus type 1 (HSV-1) is an accessory gene that encodes a component of the tegument. Homologs of this protein have been identified in the alpha, beta, and gamma herpesvirus subfamilies, although their functions are unclear. To clarify the functions of UL21, we generated a UL21-null HSV-1 mutant. Growth analysis showed that the synthesis of infectious UL21-null HSV-1 in glial cells was delayed and that the overall yield was low. The plaque sizes of the UL21-null mutant were smaller than those of wild-type HSV-1. We identified several candidate UL21-interacting proteins, including intermediate filaments, by yeast two-hybrid screening. The distribution of glial fibrillary acidic protein (GFAP), which is the main component of intermediate filaments, was altered in UL21-null mutant-infected glial cells compared to wild-type virus-infected cells. These results will help clarify the function of UL21 and broaden our understanding of the life cycle of HSV.